Effect of Cadmium Sources on the Solvothermal Synthesis of Nano CdS - Ma, Shaodan; Gao, Faming; Hou, Li (Asian Journal of Chemistry, 2011)
The CdS nanorods have been synthesized successfully using the solvothermal method. The effects of cadmium sources on the synthesis of CdS nanopaticles have been investigated. The microstructure, morphologies and compositions of the as-prepared product were characterized by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED) and UV-visible absorption spectra. All the investigations demonstrated that cadmium source play an important role in the synthesis of nano CdS.